Pathogenicity of Trichomonas hominis in Kenya - Estambale, Benson B.; Chunge, CN.; Pamba, HO; Munanga, P.; Kangethe, S. (My University, 1988)
An in vitro study of the antinematodal action of two groups of compounds which act on the receptor complex of the inhibitory neurotransmitter, Gamma-aminobutyric acid (GABA) in mammalian systems is described. The compounds, Ivermectin and two benzodiazepines, Diazepam and a water soluble Midazolam were tested singly or in combination against two microfilarial parasites Onchocerca lienalis (closely related to Onchocerca volvulus) and Brugia pahangi. The combination of ivermectin and diazepam at a concentration of 0.1 microgram/ml and 33 micrograms/ml respectively achieved the same effect on microfilarial motility as when ivermectin was given at 1 microgram/ml alone or diazepam at 66 micrograms/ml alone. Similarly when the combination of ivermectin at 0.1 microgram/ml and midazolam at 10 micrograms/ml was used it achieved the same effect as ivermectin at 1 microgram/ml alone or midazolam at 33 micrograms/ml alone. This showed that both benzodiazepines had a synergistic effect on the activity of ivermectin. The microfilariae of B. pahangi were insensitive to both groups of compounds at all concentrations used.